Contribution of IDLC in addressing financial inclusion gaps in financing scheme accessibility - Zaman, Barira Nafisa (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.